Laboratory Operational Management (OPMI) and Chemical Storage Database (CSDB) in laboratory - Ahmad, Rafidah; Mat Adam, Muhammad Ainol Naim; Mohar, Nur Hasrina; Mohd Mokhtar, Siti Fatimah; Ibrahim, Sarah; Mohd Johari, Nur Hazirah; Ahmad @ Hashim, Faridda Hannim; Ilias, Norashikin; Md Yusof, Jastina (Pusat Pengurusan Penyelidikan dan Instrumentasi (CRIM) Universiti Kebangsaan Malaysia, 2017)
An improper documentation of laboratory operation and management results in non-uniformity of workload, complexity and difficulty of tasks especially in terms of procurement, storage and record management. Additionally, the increasing of equipment units accompanied by manual and multi-packaged maintenance also contributes to the difficulties in administration, hence demands an effective and systematic documentation system. Furthermore, the higher of unregulated supply of chemicals in laboratories has made an inconvenience management and record control for the relevant parties. These problems have influence the updating, finding and accessing of chemical information and records due to inefficient record management. To ensure the laboratory comply with the authority’s rules, the implementation of new well-ordered system that comparable with Quality Management System (QMS) is crucial so that the laboratory operations is manageable. This new internal system that cover a number of key aspects such as the management of equipment inventories, chemicals and laboratory are established and regulated through INBIOSIS's Laboratory Operational Management (OPMI). INBIOSIS’s OPMI was introduced 3 years after the establishment of INBIOSIS in 2005. Throughout the year, the ideas and experience has sparks our innovation towards the centralised database management of chemicals inventory which called as Chemical Storage DataBase (CSDB). This database system is able to accommodate the full range of chemical information in laboratories that facilitates updating, storing information, searching and improving data access. This model is capable of promoting on-line and paperless data management and enhancing operational efficiency through time, energy and cost savings. With the well-establishment of those models, we have successfully awarded as the winner of Anugerah Tempat Kerja Kondusif 2016 and Anugerah Tempat Kerja Selamat 2016.